BUDAYA ORGANISASI PEMODERASI PENGARUH PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA PERUSAHAAN BERBASIS BALANCED SCORECARD - Yessi Puspitha, Made; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
Rural Banks (BPR) need to pay attention to the application of the principles of good corporate governance and organizational culture to enhance the company's performance-based balanced scorecard. This study aimed to get empirical evidence of organizational culture as the moderating influence of the principles of good corporate governance on corporate performance balanced scorecard based on BPR in Badung. Data collection method in this research is a survey method using a questionnaire and interview techniques. The sampling method using saturated sample. The sample was 52 BPR. The analysis technique used in this study is Moderated Regression Analysis. Results of this study show that the principles of good corporate governance positively affects company performance balanced scorecard based on BPR in Badung and the organizational culture can strengthen influence the direction of the principles of good corporate governance on corporate performance balanced scorecard based on BPR in Badung.
Keywords: good corporate governance, organizational culture, balanced scorecard